Mikhail Gorbachev - Butson, Thomas G. (New York Chelsea House, 1986)
Depicts the life and political career of Mikhail Gorbachev and examines his struggle to gain power and become leader of the Soviet Union
Includes Bibliography references and index
Keywords: Gorbachev, Mikhail Sergeevich -- 1931-; Heads of state -- Soviet Union -- Biography